Skeletal Muscle-Restricted Expression of Human SOD1 in Transgenic Mice Causes a Fatal ALS-Like Syndrome - Martin, Lee J.; Wong, Margaret (Frontiers in Neurology, 2020)
Amyotrophic lateral sclerosis (ALS) is a fatal heterogeneous neurodegenerative disease that causes motor neuron (MN) loss and skeletal muscle paralysis. It is uncertain whether this degeneration of MNs is triggered intrinsically and is autonomous, or if the disease initiating mechanisms are extrinsic to MNs. We hypothesized that skeletal muscle is a primary site of pathogenesis in ALS that triggers MN degeneration. Some inherited forms of ALS are caused by mutations in the superoxide dismutase-1 (SOD1) gene, that encodes an antioxidant protein, so we created transgenic (tg) mice expressing wild-type-, G37R-, and G93A-human SOD1 gene variants only in skeletal muscle. Presence of human SOD1 (hSOD1) protein in skeletal muscle was verified by western blotting, activity gels, and immunofluorescence in myofibers and satellite cells. These tg mice developed limb weakness and paresis with motor deficits, limb and chest muscle wasting, diaphragm atrophy, and age-related fatal disease with a lifespan shortening of 10-16%. Brown and white adipose tissue also became wasted. Myofibers of tg mice developed crystalline-like inclusions, individualized sarcomere destruction, mitochondriopathy with vesiculation, DNA damage, and activated p53. Satellite cells became apoptotic. The diaphragm developed severe loss of neuromuscular junction presynaptic and postsynaptic integrity, including decreased innervation, loss of synaptophysin, nitration of synaptophysin, and loss of nicotinic acetylcholine receptor and rapsyn. Co-immunoprecipitation identified hSOD1 interaction with rapsyn. Spinal cords of tg mice developed gross atrophy. Spinal MNs formed cytoplasmic and nuclear inclusions, axonopathy, mitochondriopathy, accumulated DNA damage, activated p53 and cleaved caspase-3, and died. Tg mice had a 40-50% loss of MNs. This work shows that hSOD1 in skeletal muscle is a driver of pathogenesis in ALS, that involves myofiber and satellite cell toxicity, apparent muscle-adipose tissue disease relationships. It also identifies a non-autonomous mechanism for MN degeneration explaining their selective vulnerability as likely a form of target-deprivation retrograde neurodegeneration.